Case Suspension and Binary Complement Structure in French. - Herschensohn, Julia (Current Issues in Linguistic Theory Ser. ;, 1996)
Adopting the theoretical framework of the minimalist program, this study of syntactic limitations on complement configuration investigates the link between thematic external arguments and case. Using evidence from pronominal, psychological experiencer, and inalienable constructions, it argues that both accusative and dative are structural cases in French and that this duality is reflected in a parallel limit on argument projection. Larson's single complement hypothesis, which allows a maximum of two internal arguments, provides the theoretical justification for this proposal. The testing groun.